Application of Phonics Method for Early Literacy Development of Preschool Children - Indriani, Ida Septi; Christianti, Martha; Hayati, Nur (FKIP Universitas Lampung, 2025)
Abstract: Aplication of Phonics Method for Early Literacy Development of Preschool Children. Objectives: This study aims to analyze the effectiveness of the phonics method in improving early childhood early literacy in Indonesia and identify the role of collaboration between teachers and parents in supporting its successful implementation. Early literacy is an important foundation for children's reading and writing skills, particularly in understanding the relationship between letters and sounds. Literacy challenges in Indonesia include poor teacher training and adaptation of teaching methods to suit the local context. Methods: The research method used a systematic literature review (SLR) based on PRISMA guidelines to screen and analyze 20 relevant articles from various sources. Articles were analyzed in depth using the Rayyan app, identifying key themes, namely the effectiveness of phonics methods and the role of collaboration in supporting literacy. Findings: Shows that the phonics method significantly improves children's reading and spelling skills by teaching the systematic relationship between letters and sounds. Local research supports these results, for example the “CBI FONIK” method and audiovisual-based media are effective in improving early childhood literacy skills. Collaboration between teachers and parents plays an important role in creating a supportive literacy environment both at school and at home, accelerating children's learning progress. Conclusion: The phonics method is effective in improving children's early literacy with support from teacher training and adaptation to local needs. Teacher and parent collaboration is necessary for successful implementation, providing a strong foundation for future learning. Keywords: early childhood literacy, phonics method, phonological awareness, teacher and parent collaboration.